Assessing the Effectiveness of Biotechinical Slope Stabilization Methods in Landslide Prone Areas - Prisca Nakinkunda (Uganda Christian University, 2025)
This research was conducted in Kasika Village with the primary objective of assessing the effectiveness of various biotechnical slope stabilization methods in landslide- prone areas. The study was motivated by the increasing problem of slope instability in the region, which has led to loss of lives and the destruction of critical community infrastructure, including roads. The research aimed to identify sustainable and environmentally friendly solutions for stabilizing vulnerable slopes. The study was guided by three key objectives: to evaluate the susceptibility of slopes to landslides in the affected areas, to determine the factor of safety of the slope before failure, and to assess the effectiveness of biotechnical slope stabilization techniques. The Analytical Hierarchy Process (AHP) was employed to develop a landslide susceptibility map achieving an AUC of 0.85 while the Morgenstern-Price method of slices was used to calculate the factor of safety under both saturated and normal soil conditions. Findings revealed that the studied slope was highly unstable and prone to landslide with a factor of safety of 0.885 for normal conditions and 0.955 for saturated conditions. The research recommended the implementation of brush layering using bamboo live cuttings (Oldeania alpina) as a sustainable biotechnical stabilization method to enhance slope stability in the area.
Undergraduate